Biomechanical and clinical outcomes in response to inpatient multidisciplinary hip and groin rehabilitation in UK military personnel. Issue 4 (22nd February 2021) - Allan, Richard; Cassidy, R P; Coppack, R J; Papadopoulou, T; Bennett, A N
Abstract : Introduction: Hip and groin related pain is a common complaint among the military population across UK Defence Rehabilitation and addressing associated biomechanical dysfunction is a key treatment goal. Personnel are exposed to complex occupational loads, therefore assessing movement during demanding tasks may expose biomechanical deficits. Observing biomechanical and clinical outcomes in response to treatment is therefore an important consideration. The aims were to examine clinical and biomechanical outcomes prior to (T1 ) and 12 weeks post (T2 ) inpatient rehabilitation and explore the influence of pathological subgroup. Methods: Prospective cohort study as part of a clinical service evaluation of 25 patients undergoing treatment for hip and groin related pain. Three-dimensional motion capture (3DM) during a single-leg squat, hip strength and patient-reported outcome measures were collected at T1 and T2 . Results: Increased abductor and external rotator strength with reductions in contralateral pelvic drop (1.9°; p=0.041) at T2 on the injured side. Pain reduced by 9.6 mm (p=0.017) but no differences were found for Non-Arthritic Hip Score (NAHS). No statistically significant differences were found between pathological subgroups. Kinematic profiles display variation between diagnostic subgroups and response to treatment. Conclusion: Strength and pain improved with treatment in this service evaluation although biomechanical adaptation and NAHS remain inconclusive. Small and uneven sample size prevents a firm conclusion regarding the effect of pathological subgroupings, however, the data can be considered hypothesis generating for future, larger studies to integrate 3DM for monitoring response to rehabilitation in pathological subgroups to support clinical decision making.